Duration of the susceptibility of pruning wounds of different ages to infections by Phaeomoniella chlamydospora on grapevine cv. Cabernet Sauvignon in Central Chile - Díaz, Gonzalo A.; Latorre, Bernardo A. (Frontiers in Fungal Biology, 2022)
Grapevine trunk diseases (GTDs) are one of the most important phytosanitary problems that affect grapevines (Vitis vinifera) worldwide. In Chile, Phaeomoniella chlamydospora is the major fungal trunk pathogen associated with GTDs. In the vineyards, the natural infections by P. chlamydospora are associated with air-borne conidia dispersed onto fresh pruning wounds from pycnidia. These pruning wounds are considered an important entrance for fungal trunk pathogens such as P. chlamydospora in the host in the field. However, the duration of the susceptibility of grapevine annual pruning wounds to P. chlamydospora is still unknown in Chile. Therefore, this study aimed to evaluate the period of susceptibility of pruning wounds of different ages to artificial infection of P. chlamydospora on grapevine cv. Cabernet Sauvignon, Central Chile. Artificial inoculations of a conidial suspension (105 conidia/mL) of P. chlamydospora were used to determine the susceptibility of pruning wounds of different ages, from 1, 15, 30, and 45 days after pruning. The experiments were conducted on lignified cuttings in a greenhouse, and on vine spurs in two vineyards (Buin and Nancagua, Central Chile) during two consecutive seasons. The results indicated that the pruning wounds of grapevine cv. Cabernet Sauvignon were very susceptible to infections by P. chlamydospora, with percentage of pruning wounds infected from 97 to 71% for cuttings, and 96% to 60% for spurs, during the first 15 days after pruning. However, the susceptibility of pruning wounds of different ages in cuttings and spurs of grapevine, generally decreased as the time from pruning to inoculation increased. However, the pruning wounds remained susceptible to artificial inoculation by P. chlamydospora for up 45 days after pruning with percent of wounds infected from 8.0 to 12.2, and 8.3 to 18.8% on cuttings and spurs of grapevine, respectively. This study constitutes the first research focalized on the susceptibility of pruning wounds of various ages of grapevine cv. Cabernet Sauvignon to artificial inoculations by P. chlamydospora in Central Chile.